2009
DOI: 10.1002/jmri.21883
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of external carotid artery and its branches: Non–contrast‐enhanced MR angiography using balanced steady‐state free‐precession sequence and a time‐spatial labeling inversion pulse

Abstract: Purpose: To evaluate visibility of the external carotid artery (ECA) and its branches using three-dimensional (3D) balanced steady-state free-precession (SSFP) MR angiography with a time-spatial labeling inversion pulse (Time-SLIP), and to provide an optimal value of the inversion time (TI). Materials and Methods:Peripheral-pulse-wave-gated 3D balanced SSFP images were obtained in 20 healthy volunteers. Images with a Time-SLIP using four different TIs (600, 900, 1200, and 1500 ms) and without a Time-SLIP, refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…The subtraction has the advantage of completely removing the background tissue signal. ASL has been proposed for MR angiographic applications in the cerebral vasculature and renal arteries (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, spin-labeling approaches have been used to assess hemodynamic function, including infl ow in the vessels and arrival times to the tissue ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The subtraction has the advantage of completely removing the background tissue signal. ASL has been proposed for MR angiographic applications in the cerebral vasculature and renal arteries (16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Furthermore, spin-labeling approaches have been used to assess hemodynamic function, including infl ow in the vessels and arrival times to the tissue ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Lanzman et al also reported that this approach provided high sensitivity (100%) and high specificity (88%) for the detection of transplant renal artery stenoses (56). SSFP angiography with ASL is also used for the portal vein (Fig 19) (57) and head and neck arteries (58). Images of the hepatic vein and inferior vena cava can also be obtained by using another slab-selective IR pulse (59).…”
Section: Asl With Ssfp Techniquementioning
confidence: 96%
“…As a consequence, the leading edge of the created blood bolus might have already entered the imaging volume at the time of acquisition of the first dynamic. Pulsed ASL methods may overcome this limitation, as a blood bolus is created by the inversion of a large blood volume at once proximal to the image region [15,31,32], however, spatial selectivity is restricted.…”
Section: Discussionmentioning
confidence: 97%